Soldiers a history of men in battle - Keegan, John 1934-2012; Holmes, Richard 1946-2011 (Viking, 1986)
Celebrated military historian, John Keegan, and co-author, Richard Holmes, chart the changes in the conduct of warfare through history with an instructive combination of analysis and illustration. In the process they reveal that what has not changed is that an army ultimately has to depend on the courage and determination of its fighting men.
Keywords: Combat; Soldiers; War; Soldat; Geschichte; Schlacht